Polymicrobial bacteremia caused by Ewingella americana (family Enterobacteriaceae) and an unusual Pseudomonas species. - Pien, F D (1983)
Ewingella americana and a Pseudomonas species were isolated from three sets of blood cultures from a 41-year-old patient after coronary bypass surgery. This is the first well-described case of bacteremia due to E. americana. Based on data from 31 strains, a detailed description of E. americana is given.